Ensino lúdico da citologia para o ensino fundamental anos finais com suporte da computação desplugada - Barbosa, Lucivan Néri (2023)
The present work, entitled "The playful teaching of cytology for Elementary School Final Years with the support of unplugged computing", linked to the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo (PPGECM - UPF), in the line research project Information, Communication and Interaction Technologies applied to the teaching of Science and Mathematics, was developed together with the Escola Estadual de Ensino Fundamental Castro Alves, part of the public education network, located in the city of Cerejeiras-RO, during after-school hours with 6th grade students year of Elementary School Final Years, in the urban area. The guiding question of the dissertation was: how to use play with the support of unplugged computing in cytology classes in Elementary School Final Years, in order to improve the learning process? In view of this, the main objective was to develop the teaching of cytology in a playful way and with the support of unplugged computing, providing new learning strategies for students in the 6th year of Final Years Elementary School, given the different pedagogical practices and the new technologies. Based on the Three Pedagogical Moments (Initial Questioning, Organization of Knowledge and Application of Knowledge) the methodological proposal was structured in a didactic sequence of 11 meetings with playful activities, unplugged computing, technical visit to a Science/Biology laboratory, production of reports and construction of edible models, aiming to stimulate the learning of cytology and develop Computational Thinking (CP). The research methodology was based on a qualitative approach, of an applied nature; As for the objectives, it was characterized by exploratory and participatory research. For this, some steps were carried out, such as: bibliographical research, definition of classes and production of the Educational Product (EP). For data collection, a conversation circle was held, in order to collect prior knowledge, reports in the research teacher's logbook, activities developed by students, technical visit report and photographic records throughout the application of the research project. The results showed that playfulness and Unplugged Computing, in the face of the public of the new technological era, become allies, and can be an important teaching strategy making it possible to make the study of cytology more dynamic, engaging and fun, since, at various times , showed evidence of learning, such as motivation, collaboration, communication, understanding, retention of content, in addition to awakening curiosity and the development of students' cognitive and socio-emotional skills. Finally, the educational product, an additional document for this dissertation, is available on the educational products portal of the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo and on the EduCapes website.